Radiation-induced caries as the late effect of radiation therapy in the head and neck region - Dobroś, Katarzyna; Hajto-Bryk, Justyna; Wróblewska, Małgorzata; Zarzecka, Joanna (Contemporary Oncology/Współczesna Onkologia, 2016)
Overall improvement in the nationwide system of medical services has consequently boosted the number of successfully treated patients who suffer from head and neck cancer. It is essential to effectively prevent development of radiation-induced caries as the late effect of radiation therapy. Incidence and severity of radiation-induced changes within the teeth individually vary depending on the patient’s age, actual radiation dose, size of radiation exposure field, patient’s general condition and additional risk factors. Inadequately managed treatment of caries may lead to loss of teeth, as well as prove instrumental in tangibly diminishing individual quality of life in patients. Furthermore, the need to have the teeth deemed unyielding or unsuitable for the application of conservative methods of treatment duly extracted is fraught for a patient with an extra hazard of developing osteoradionecrosis (ORN), while also increasing all attendant therapeutic expenditures. The present paper aims to offer some practical insights into currently available methods of preventing likely development of radiation-induced caries.